Medicinal Protection in Elderly Patients in Ophthalmous Surgery Practice - B. K., Kholbekov (American Journal of Biology and Natural Sciences, 2024)
the relevance of the problem of arterial hypertension (AH) is determined by its high frequency in the population, the impact on health, performance and life expectancy of the population. The purpose of the study. To improve existing methods of preoperative preparation and evaluate the effectiveness sedation and neuroleptanalgesia (NLA) in elderly patients with concomitant hypertension to prevent the risk of cardiovascular complications in ophthalmic surgery. Materials and methods. Clinical observations cover 150 patients aged 60 to 89 years (74.7±0.5) who were treated for surgical treatment for age-related cataracts in the ophthalmology department of the clinic of Samara State Medical University. Results. In all patients with hypertension, target blood pressure values were clinically achieved against the background of selected antihypertensive therapy. Arterial hypertension before surgery in patients of group II indicated a pressor reaction of the cardiovascular system (CVS) in response to psychoemotional irritation and associated short-term fear of surgery. Conclusions. The results of the study allow us to state that adequate hypotensive therapy in combination with drugs that reduce mental and emotional stress in the preoperative period, the exclusion of visual contact, psychoemotional stress through sedation and neuroleptanalgesia in waiting rooms allow us to achieve stabilization of the clinical condition of patients, clearly correlating with improvement of hemodynamic parameters.